(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
In this article, the moral foundations of marriage and family, its role in the education of young people, the influence of the psychological, socio-spiritual environment of the family on the upbringing of children, and the improvement of the spiritual and moral principles of the attitude to the family in the psychology of young people are fully described.